PEMANFAATAN AMPAS KELAPA SEBAGAI BAHAN PANGAN SUMBER SERAT DALAM PEMBUATAN COOKIES UBI JALAR UNGU (Utilization of Coconut Pulp as fiber source in Purple Sweet Potato Cookies) - Niga Wardani, Ema; Sugitha, I Made; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
Coconut pulp is a byproduct of coconut milk product. Coconut pulp can be processed into coconut flour that used as raw materials of purple sweet potato cookies. The purpose of this research is to observe the ratio effect of purple sweet potato flour and coconut flour to produce the best characteristics of purple sweet potato cookies. This research used completely randomize design with purple sweet potato flour and coconut flour ratio 100:0, 90:10, 80:20, 70:30, 60:40, 50:50. Treatment was repeated three times to obtain 18 units experiment. The anova used to analysis of the data and followed by DMRT if there are significant effect. The best result of the research was produced by the ratio of 90:10 for purple sweet potato flour and coconut flour that contain of water 2,87%, ash 1,43%, fat 46,58%, protein 2,88%, carbohydrate 46,24%, crude fiber 7,69%, colour was purple (4,00), texture was crispy (4,07), flavour was rather like (5,40), taste was like (5,53), and overall acceptance was rather like (5,40).
Keywords: cookies, coconut flour, purple sweet potato flour